MODEL DAN PRAKTEK PROSES KEBIJAKAN STRATEGIS DI INDONESIA : STUDI KASUS MANAJEMEN STRATEGIS DI PEMERINTAH PUSAT INDONESIA (2009-2012) - Affandy Agusman Aris (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Since 1998, the Indonesian government has introduced an approach to Strategic Management under Government Regulation No. 108/200 government has not evaluated the experience with this strategy. However, in 2009, President Yudhoyono's administration introduced a new approach called Medium Term Development Plan (RPJMD) -Planning Long Term Development. The interesting question regards compliance with the government's strategic plan. In other words, is the continued implementation of the strategic plan? In this paper, the authors investigated the experiences with efforts to introduce the model and practice of Strategic Management in the public sector Indonesia, in particular aspects of the process and tools. The method used in this study is historical and descriptive using casual circle model system dynamics method. The study found that the strategic planning model implemented by the government is a linear process model associated with the key success factors of leadership, professional coordination between government units and complete process monitoring and instruments: planning, implementation and evaluation